Concerns, Contributions, and Challenges of Critical Pedagogies in ELT: A Literature Review - Vanegas Garzón, Sindy Lissette; Bedoya Ríos , Nohemy Marcela (Universidad Pedagógica y Tecnológica de Colombia, 2023)
Critical pedagogies have been researched in many knowledge areas, particularly in social sciences. However, in the field of English language teaching, pedagogical and didactic models that implement critical perspectives are scarce. This review attempts to characterize trends of discussion addressed in the scientific literature on critical pedagogies in the teaching of English from 2011 to February 2023. For this, 55 articles available in Scopus, Eric, and Scielo databases were analysed. Four categories were identified: 1) Critical pedagogical practices in ELT, 2) Analysis on the teacher role and education, 3) Principal concerns which yield the introduction of critical pedagogies to ELT field, and 4) Limitations and challenges for critical pedagogies in ELT. This paper stresses the need to deepen and expand research in the field of ELT around the category of critical pedagogies as a possibility to contribute to the English teaching practices, mainly when included in the teachers’ education processes.